2023
DOI: 10.24818/tbj/2022/12/4.02
|View full text |Cite
|
Sign up to set email alerts
|

To reach sustainable justice with Millennials: example of Ukraine

Abstract: Sustainable development became an essential part of our world since we realized the fragility and limits of our system, dangerous of resource exhaustion, and insistently looking for the way to stabilyze our life and life of our descendents, to restrict risks of collapses. Last years’ catastrophes – the pandemic of COVID-19 and the war in Ukraine, both are still existed, show us undoubtedly that we have to be more careful using our resources and develop our relations in economics and politics. In this article a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One approach may be to broaden the sampling of Gen Zs to include multiple samples from across the United States to establish a national Gen Z profile, such as what was conducted using a Millennials sample (Weber et al, 2019). Or, research could broaden to focus on other countries and the Gen Zs' data found there, such as in Ukraine (Khotynska‐Nor, 2022), or in Hong Kong (Snelgrove et al, 2021). This research could be further extended through the exploration of a global (multiple‐country) Gen Z sample, again much like the research investigating Millennials, to see if cultural or other geographic variations might influence Gen Zs' identity (Weber & Urick, 2021; Zaid et al, 2022).…”
Section: Discussion Implications Future Research and Conclusionmentioning
confidence: 99%
“…One approach may be to broaden the sampling of Gen Zs to include multiple samples from across the United States to establish a national Gen Z profile, such as what was conducted using a Millennials sample (Weber et al, 2019). Or, research could broaden to focus on other countries and the Gen Zs' data found there, such as in Ukraine (Khotynska‐Nor, 2022), or in Hong Kong (Snelgrove et al, 2021). This research could be further extended through the exploration of a global (multiple‐country) Gen Z sample, again much like the research investigating Millennials, to see if cultural or other geographic variations might influence Gen Zs' identity (Weber & Urick, 2021; Zaid et al, 2022).…”
Section: Discussion Implications Future Research and Conclusionmentioning
confidence: 99%